Pelatihan Pewarnaan Alami Untuk Pembuatan Kain Tenun di Kecamatan Nekamese, Kabupaten Kupang - Arvinda C.Lalang; Dewi Lestarani; Heru Christianto; Dorthea M.W.Nay (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The making of traditional woven fabrics has traditionally used natural coloring. But at present, the manufacture of woven fabrics has been greatly influenced by the use of yarn from factories that have been colored with textile dyes. The use of colored yarn from the factory is due to the use of natural materials that fade quickly. The traditional knowledge of natural coloring began to forgotten. The Nekamese area has the potential for plants that can used as natural dyes. In addition, there are also natural ingredients that can be used as a mixture so that the color of woven fabrics does not fade. However, the partners do not have the knowledge and skills to utilize plants as natural dyes for making woven fabrics.